The Willingness of Individual Taxpayers to Pay Taxes - Wulandari, Dian Sulistyorini; Karomah, Laelatul (Proceeding International Pelita Bangsa, 2023)
This study aims to determine whether the variable awareness of paying taxes, knowledge and understanding of tax regulations, and level of perception of the effectiveness of the tax system have an effect on the willingness to pay taxes by taking a sample of 99 taxpayers registered at KPP Pratama Cibitung. The type of research used in this study is research. quantitatively with the sampling method of random sampling, namely by taking a sample of taxpayers who are registered at KPP Pratama Cibitung randomly. The results of this study show that awareness of paying taxes partially has a positive and significant effect on willingness to pay taxes, knowledge and understanding of taxation regulations partially have a positive and significant effect on willingness to pay taxes, perceptions of the effectiveness of the taxation system partially have no effect on willingness to pay taxes, and the level of trust in the government and law partially has no effect on willingness to pay taxes.